Metales pesados en el agua lluvia (2017)
The present research provides a review of heavy metals in rainwater around the world. The content of this paper is divided into three main chapters: (i) the identification of common heavy metals in rainwater; (Ii) the average concentrations of heavy metals in rainwater; (Iii) Comparison of permissible values of heavy metals in water according to different national and international standards of drinking water and reuse. The results of this work identified four heavy metals in rainwater that are harmful to human health.